Current opportunities of primary endodontic treatment of chronic apical periodontitis with endo-perio origin - I. V. Kornetova; A. V. Mitronin; I. M. Rabinovich (LLC "Endo Press", 2021)
Primary endodontic treatment of chronic apical periodontitis caused by primary perio lesion, a frequent case in the dental clinical practice. This situation is a dilemma when drawing up a comprehensive treatment plan for a patient, taking into account the pathogenesis of the disease. Extracting or saving a tooth is still a controversial issue for dental surgeons and therapists. To obtain a successful result, it is necessary to carry out high-quality endodontic and periodontal treatment. This article represents a clinical case of primary endodontic treatment of tooth 1.7 with endo-perio lesion. At the final stage, the final result of the treatment is presented in 2 weeks. This article will help dentists acquire additional knowledge necessary for making decisions and choosing treatment tactics in difficult clinical situations.